The Determination of Phytoextraction Capacity Using Lavender (Lavandula latifolia) Plant in Nickel-Contaminated Soils - CAN, Merve; EREN, Abdullah (ISPEC Tarım Bilimleri Dergisi, 2024)
This study was conducted to evaluate the suitability of Lavender (Lavandula latifolia) plant for the remediation of soils contaminated with nickel (Ni). The Lavender plant has the potential to clean contaminated soils by absorbing pollutants through a method called phytoextraction. In the research, Ni-contaminated soils were prepared under controlled conditions, and Lavender plants were grown in these soils. The growth and development of the plants were monitored, and it was investigated whether the plants absorbed Ni from the soil and accumulated it on the plant. Increasing doses of Ni (0-200-400-600-800 mg kg-1) were applied in solution form, and pot soils were incubated for one week at 60-65% of field capacity. Then, seedlings in peat medium were transferred to pots and grown under controlled conditions for 6 weeks. It was determined that the plant age, fresh and dry weight, and height increased with 200 and 400 mg Ni kg-1 applications compared to the control groups, while there was a decrease with 600 and 800 mg Ni kg-1 applications. The lowest concentrations of Ni (mg kg-1) in plants and Ni content (µg plant-1) were observed in the control group (0 mg Ni kg-1), while the highest values were found in the 800 mg Ni kg-1 application. It was found that the concentrations of 400 mg Ni kg-1 (124 µg plant-1), 600 mg Ni kg-1 (137 µg plant-1), and 800 mg Ni kg-1 (150 µg plant-1) exceeded critical levels for plants, yet the plants remained alive at these concentrations. The phytoextraction ability of plants refers to their ability to absorb and retain harmful or polluting substances from the soil. Lavender may be among the plants that have phytoextraction potential for metals like Ni. However, the phytoextraction ability can vary depending on the species of the plant, growth conditions, and the pollutant applied. The research results demonstrated that the Lavender plant effectively absorbed Ni from the soil and accumulated it on the plant. This suggests that Lavender can be used for the remediation of soils contaminated with Ni.